The Influence of Company Size, Asset Structure, Company Growth And Profitability on Debt Policy in The Food and Beverage Industry Sub-Sector (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
Debt policy is one of the decisions that must be considered by a company. There are strengths and weaknesses of the debt policy undertaken which can have an impact on the company itself and investors who will invest their capital in the company. Managers must determine a good debt policy by taking into account the right risks and proportions in order to increase the value of the company. Therefore this study aims to determine the determinants of debt policy in the food and beverage industry sub-sector in the 2014-2018 period. To find out the factors that influence debt policy, this study uses panel data regression analysis with a population of 23 companies and in the sample selection method used is purposive sampling technique. The results showed that there are two variables that affect debt policy, including tangibility which has a positive influence on debt policy and company growth has a negative effect on debt policy. While company size and profitability have no effect on debt policy